New/s Design: Informing Future Design Processes by Understanding Media Reporting of Medical Errors with Medical Devices [invited paper] - Myketiak, Chrystie; Concannon, Shauna; Curzon, Paul (EAI Endorsed Transactions on Smart Cities, 2015)
In this paper we present a case study of media reporting about medical technology issues. We discuss two incidents involving human error with medical devices that resulted in infant deaths, and their relevance for the medical device design and mobile health communities. Our analysis into the language and discourses of news reporting shows that the news narratives of these incidents emphasise human aspects of the error and neglect device issues. Better design is not conceptualised as an option in these narratives, even when systemic issues are discussed in relation to errors with devices. However, there is a possibility for better design solutions if practitioners are aware of the discursive construction of errors, including how critical incidents are framed and developed in news discourse.
Keywords: critical discourse analysis; human error; news reporting; medical devices; patient safety; sociolinguistics